SOYABEAN RESPONSE TO DIFFERENT LEVELS OF APPLIED PHOSPHORUS AND NITROGEN IN THE SOUTHERN GUINEA SAVANNA OF NIGERIA - OLOFINTOYE, J.A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Two cultivars of soyaben (Glycine max (L) Merrill) were grown for two years under field conditions to evaluate the effects of N and P on nodulation and yield components. Inhibitory effects of N and on nodulation were observed. Yield components of the profuse nodulating cultivar (TGM 597) were negatively correlated, while those of the poor nodulating cultivar (TGX 536 - 62D) were positively correlated with applied N, indicating differential cultivar response to N. Phosphorus increased nodulation and yield of the two cultivars. There were indications that the optimum level of P for optimum soyabean yield would vary significantly with the level of the native soil available P, emphasizing the importance of soil analysis in P recommendations for soyabean.